Positive Solutions for Schrödinger-Poisson Systems with Sign-Changing Potential and Critical Growth - Pengfei He; Hongmin Suo (Journal of Function Spaces)
In this paper, we study the existence of positive solutions for Schrödinger-Poisson systems with sign-changing potential and critical growth. By using the analytic techniques and variational method, the existence and multiplicity of positive solutions are obtained.